Inhibition of miR-325 inhibits KIF20B expression and the colorectal cancer cells’ invasion & proliferation - Qi-Qi Zheng; Wen-Feng Lin (BMC Cancer)
Abstract Objective This study aimed to investigate the effect of miR-325 on KIF20B expression and its role in the invasion and proliferation of colorectal cancer cells. Methods Colorectal cancer HCT116 cells were cultured and transfected with a miR-325 inhibitor. KIF20B expression was assessed using quantitative polymerase chain reaction (qPCR) and western blotting. Cell proliferation was assessed with the Cell Counting Kit-8 (CCK8) assay, while invasion was evaluated using Transwell and scratch wound healing assays. The expression levels of the invasion-related proteins Matrix Metalloproteinase-2 (MMP-2) and MMP-9 were also analyzed. Results The q-PCR and western blot results demonstrated that KIF20B expression was significantly reduced by miR-325 inhibition. The CCK8 assay revealed that miR-325 inhibition decreased cell proliferation. Furthermore, Transwell and Scratch Wound Healing assays showed that miR-325 inhibition suppressed the invasive capacity of colorectal cancer cells. The inhibition of miR-325 also led to decreased expression levels of MMP-2 and MMP-9. Conclusion miR-325 inhibition effectively suppresses KIF20B expression, reducing the invasion and proliferation of colorectal cancer cells, suggesting miR-325 as a potential therapeutic target.